2014
DOI: 10.1108/mf-06-2012-0128
|View full text |Cite
|
Sign up to set email alerts
|

Underlying asset liquidity, heterogeneously informed investors, and REITs excess returns

Abstract: Purpose – Real estate investment trust (REIT) stocks are well known for limited management discretion in investment, financing, and payout policies, implying little information asymmetry between informed and uninformed investors. Besides, due to the renowned illiquidity and complexity of physical real estate markets, investors may be heterogeneously informed. The authors aim to investigate these arguments using REIT panel data from 1993 to 2010. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…One of the most common scope ofstudies in REITs performance is comparing performance of one or some REITs companies within one jurisdiction (Akinsomi, Ong, Ibrahim, & Newell, 2016;Aro-gordon, 2015;Asteriou & Beigazi, 2013;Bene, Anderson, & Zumpano, 2009;Brown, 2000;Compton, Johnson, Kunkel, & Compton, 2006;Escobari & Jafarinejad, 2016;Hartzell, Kallberg, & Liu, 2008;Hartzell, Sun, & Titman, 2014;Ho & Tay, 2016;Huerta, Jackson, & Ngo, 2015;Larson, 2005;C. Lee, Chien, & Lin, 2012;Liow & Addae-dapaah, 2010;Lu, Chen, & Liao, 2014;Olanrele, Said, & Daud, 2014;Pellerin et al, 2013;Quek & Ong, 2008;San, Heng, & Pong, 2011;Yung, Li, & Jian, 2017), with USA market is the most studied so far, which is not surprising because USA REITs market is the mature one in the world. One example is a study by (Brown, 2000) found that mortgage REITs that financed real estate investment using financial leverage had deeper negative returns compared to equity REITs that financed the investment directly.…”
Section: Reits Performance Risk and Volatilitymentioning
confidence: 99%
“…One of the most common scope ofstudies in REITs performance is comparing performance of one or some REITs companies within one jurisdiction (Akinsomi, Ong, Ibrahim, & Newell, 2016;Aro-gordon, 2015;Asteriou & Beigazi, 2013;Bene, Anderson, & Zumpano, 2009;Brown, 2000;Compton, Johnson, Kunkel, & Compton, 2006;Escobari & Jafarinejad, 2016;Hartzell, Kallberg, & Liu, 2008;Hartzell, Sun, & Titman, 2014;Ho & Tay, 2016;Huerta, Jackson, & Ngo, 2015;Larson, 2005;C. Lee, Chien, & Lin, 2012;Liow & Addae-dapaah, 2010;Lu, Chen, & Liao, 2014;Olanrele, Said, & Daud, 2014;Pellerin et al, 2013;Quek & Ong, 2008;San, Heng, & Pong, 2011;Yung, Li, & Jian, 2017), with USA market is the most studied so far, which is not surprising because USA REITs market is the mature one in the world. One example is a study by (Brown, 2000) found that mortgage REITs that financed real estate investment using financial leverage had deeper negative returns compared to equity REITs that financed the investment directly.…”
Section: Reits Performance Risk and Volatilitymentioning
confidence: 99%